Quality of Tuna Botok Pontianak in Glass Jar Packaging During Storage - Hartanti, Lucky; Rahayuni, Tri (Jurnal Biologi Tropis, 2024)
Tuna botok is a popular traditional food from Pontianak with high nutritional value, but its shelf life is short due to its susceptibility to spoilage. Proper packaging is essential to extend its shelf life and enhance the value of Pontianak's traditional foods. This study aims to evaluate the quality of tuna botok packaged in glass jars during storage. Measurements of moisture content, ash content, protein content, fat content, and total plate count were conducted on days 5, 10, 15, and 20 of storage. The results indicated that storage for up to 20 days had no effect on ash and fat content, but significantly impacted moisture and protein content. After 20 days, the total plate count remained within acceptable limits, with the product containing 66.56% moisture, 2.27% ash, 14.76% protein, and 11.78% fat.